Lipid Metabolism in Ferroptosis. Issue 8 (20th May 2021) - Lin, Zhi; Liu, Jiao; Kang, Rui; Yang, Minghua; Tang, Daolin
Abstract: Lipid metabolism is a complex biochemical process that participates in the regulation of cell survival and death. Ferroptosis is a form of iron‐dependent regulated cell death driven by abnormal lipid metabolism, leading to lipid peroxidation and subsequent plasma membrane rupture. A variety of antioxidant systems and membrane repair pathways can diminish oxidative damage, enabling survival and growth in response to ferroptotic signals. Such impairment of ferroptosis machinery is implicated in various pathological conditions and diseases, especially cancer and tissue damage. It is discussed here how lipid metabolism pathways, including lipid synthesis, degradation, storage, transformation, and utilization, modulate ferroptosis sensitivity or tolerance in different models, especially cancer. Abstract : Ferroptosis is a form of iron‐dependent regulated cell death driven by abnormal lipid metabolism, leading to lipid peroxidation and subsequent plasma membrane rupture. The processes and functions of various types of lipid metabolism in ferroptosis and the role of antioxidant systems in limiting lipid peroxidation are discussed here.